FIELD OBSERVATIONS OF THE 2015 (NOVEMBER 17, MW 6.4) LEFKAS (IONIAN SEA, WESTERN GREECE) EARTHQUAKE IMPACT ON NATURAL ENVIRONMENT AND BUILDING STOCK OF LEFKAS ISLAND - Lekkas, E.; Mavroulis, S.; Alexoudi, V. (Bulletin of the Geological Society of Greece, 2016)
On Tuesday, November 17, 2015 at 07:10:07 (UTC) a strong earthquake struck Lefkas Island (Ionian Sea, Western Greece) with magnitude Mw 6.4, depth of about 7 km and epicenter located 20 km southwest of Lefkas town. The seismic activity in the region was essentially expected after the 2003 Lefkas earthquake and the 2014 Cephalonia earthquakes. Between these earthquake affected areas, the tectonic stresses were not released after the 1948 Lefkas earthquakes. Instead, they were intensifying and accumulating until the generation of the 2015 event. It was felt in Lefkas and the surrounding region and caused the death of 2 people, the injury of 8 others, earthquake environmental effects (EEE) and damage to buildings and infrastructure. Secondary EEE were observed in western Lefkas and included ground cracks, slope movements and liquefaction. Primary effects were not detected in the field. Buildings damage were mainly observed in villages of Dragano-Athani graben in southwestern Lefkas. Among structures constructed with no seismic provisions, the stone masonry buildings and monumental structures suffered most damage, while the traditional buildings with dual structural system performed relatively well. Reinforced-concrete buildings were affected not so much by the earthquake itself but by the generation of secondary effects.